Factibilidad técnico – económico del proyecto de ampliación en la mina abigail estefania en el departamento de arequipa - Deza Castro, Carlo Salvador (2017)
Estefania concession located in the gorge Piruja, Chaparra District, Province of Caraveli, Department of Arequipa, has a system of hydrothermal veins of gold content, with variable power between 0.10 to 1.2 m. which is an evidence of mineralization. The geological survey and field observations found two areas: The first is located in the Puruja broken with proven mineral TM 5280 with 0.43 ounces per ton of gold; This area is in operation, the second zone is located west of the Puruja broken with probable ore TM 5800 with 0.23 ounces per ton of gold; this is the reason of this research; whose goal is to exploit the deposit at the lowest possible cost in compliance with mining regulations in legality, safety and the environment. In development meeting that the site is easily accessible counting on roads to the farming area with a stable gold price ensuring a positive short and medium term trend criteria are established regarding the transport of solids, method of operation, control of operations, PETS work, mine safety, etc. In the mining aspect Ensuring the operation of the mine. The metallurgical aspect, construction and installation of plant, treatment costs guarantee mineral processing, all under an appropriate approach, making an economic evaluation concludes on the feasibility of this expansion project.